2021
DOI: 10.3390/su132011302
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Spatial Heterogeneity of the Built Environment and Its Impact on the Urban Thermal Environment—Case Study of Downtown Shanghai

Abstract: Ongoing urban expansion has accelerated the explosive growth of urban populations and has led to a dramatic increase in the impervious surface area within urban areas. This, in turn, has exacerbated the surface heat island effect within cities. However, the importance of the surface heat island effect within urban areas, scilicet the intra-SUHI effect, has attracted less concern. The aim of this study was to quantitatively explore the relationship between the spatial heterogeneity of a built environment and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Studies have shown that the heterogeneity of urban and suburban surfaces, caused by the substitution of natural surfaces by large impervious surfaces during urbanization, is the fundamental reason for the formation of SUHI [ 22 , 23 , 24 ]. Urban land cover types [ 25 , 26 , 27 , 28 ] and urban forms [ 29 , 30 ] have direct driving effects on SUHI formation and development, while regional climate [ 31 , 32 ], human activities [ 29 , 33 ], and the built-up area [ 34 ] also affect the intensity and distribution of SUHI. However, these studies do not consider surface temperature directionality when calculating SUHI intensity by LST, thus measuring the urban thermal environment, which affects the accuracy of the studies to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the heterogeneity of urban and suburban surfaces, caused by the substitution of natural surfaces by large impervious surfaces during urbanization, is the fundamental reason for the formation of SUHI [ 22 , 23 , 24 ]. Urban land cover types [ 25 , 26 , 27 , 28 ] and urban forms [ 29 , 30 ] have direct driving effects on SUHI formation and development, while regional climate [ 31 , 32 ], human activities [ 29 , 33 ], and the built-up area [ 34 ] also affect the intensity and distribution of SUHI. However, these studies do not consider surface temperature directionality when calculating SUHI intensity by LST, thus measuring the urban thermal environment, which affects the accuracy of the studies to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…At a community level, the availability of green spaces impacts the environmental quality, helps with stress restoration [4,5], enhances the feeling of social safety [6], increases social interaction, and promotes property values [7]. Urban green space has been recognized as a key variable for assessing the livability of cities [8], whereas its spatial data at the finegeographical scale is difficult to generate [9]. One way of obtaining the spatial information of UCGS is to extract it from remote sensing images [10].…”
Section: Introductionmentioning
confidence: 99%